2020
DOI: 10.21203/rs.3.rs-39769/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Minimum Clinical Important Difference for Resilience Scale Specific to Cancer: A Prospective Analysis

Abstract: Background: The minimum clinical important differences (MCIDs) of resilience instruments in patients with cancer have not been comprehensively described. This study was designed to evaluate MCIDs of 10-item and 25-item resilience scales specific to cancer (RS-SC-10 and RS-SC-25).Methods: From June 2015 to December 2018, RS-SCs were longitudinally measured in 765 patients with different cancer diagnoses at baseline (T0) and 3 months later (T1). The EORTC QLQ-C30, Connor-Davidson Resilience Scale, Hospital Anxie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…The Urdu versions of both the EORTC QLQ-C30 and QLQ-BN20 tools also demonstrated acceptable construct validity, with the global quality of life domain showing significant positive correlations with resilience (r = 0.422), and significant negative correlations with depression (r = −0.541) and anxiety (r = −0.502). Previous studies have also reported similar positive correlations between QoL and resilience [34,35] and similar negative correlations between QoL and depression and anxiety in cancer patients [36,37]. In addition, the Hindi translation of the EORTC QLQ-BN20 has also demonstrated significant correlations with depression and anxiety as measured by HADS [38].…”
Section: Discussionsupporting
confidence: 53%
“…The Urdu versions of both the EORTC QLQ-C30 and QLQ-BN20 tools also demonstrated acceptable construct validity, with the global quality of life domain showing significant positive correlations with resilience (r = 0.422), and significant negative correlations with depression (r = −0.541) and anxiety (r = −0.502). Previous studies have also reported similar positive correlations between QoL and resilience [34,35] and similar negative correlations between QoL and depression and anxiety in cancer patients [36,37]. In addition, the Hindi translation of the EORTC QLQ-BN20 has also demonstrated significant correlations with depression and anxiety as measured by HADS [38].…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, some trait‐like scales, for example, subscale of Generic Elements, may not be suitable to be used in change‐focused intervention trial. Future studies should evaluate these scales' responsiveness and minimum clinical important difference in clinical trials 39 …”
Section: Discussionmentioning
confidence: 99%
“…The Cronbach's α of RS-SC-10 is 0.86. The Minimum Clinical Important Difference for RS-SC-10 is 2 points [20]. RS-SC-25 and RS-SC-10 were attached in the supplemental les.…”
Section: Sample Sizementioning
confidence: 99%